Phylogenetic evaluation of the genus Nostoc and description of Nostoc neudorfense sp. nov., from the Czech Republic - Singh, Prashant; Šnokhousová, Jana; Saraf, Aniket; Suradkar, Archana; Elster, Josef (International journal of systematic and evolutionary microbiology, 2020)
Cyanobacterial strain ARC8 was isolated from seepage coming into the river Dračice, Františkov, Czech Republic, and was characterized using a polyphasic approach. Strain ARC8 showed a typical Nostoc-like morphology and in-depth morphological characterization indicated that it is a member of the genus Nostoc. Furthermore, in the 16S rRNA gene phylogeny inferred using Bayesian inference, maximum likelihood and neighbour joining methods, strain ARC8 clustered within the Nostoc sensu stricto clade. The phylogenetic distance and the positioning of strain ARC8 also indicated that it is a member of the genus Nostoc. Furthermore, the rbcL gene phylogeny along with the 16S-23S ITS secondary structure analysis also supported the findings from the 16S rRNA gene tree. In accordance with the International Code of Nomenclature for Algae, Fungi and Plants we describe a novel species of Nostoc with the name Nostoc neudorfense sp. nov.
Keywords: taxonomy; Nostoc; polyphasic approach; DNA bakterií; RNA, Ribosomal, 16S; DNA, Bacterial; ITS; Bayesova věta; Rivers; Bayes Theorem; cyanobacteria; zastoupení bazí; Phylogeny; 16S rRNA gene; Czech Republic; řeky; Base Composition; Bacterial Typing Techniques; Sequence Analysis, DNA; techniky typizace bakterií; Česká republika; sekvenční analýza DNA; fylogeneze; RNA ribozomální 16S